Enhanced B Cell Alloantigen Presentation and Its Epigenetic Dysregulation in Liver Transplant Rejection. Issue 2 (11th December 2015) - Ningappa, M.; Ashokkumar, C.; Higgs, B. W.; Sun, Q.; Jaffe, R.; Mazariegos, G.; Li, D.; Weeks, D. E.; Subramaniam, S.; Ferrell, R.; Hakonarson, H.; Sindhi, R.
Abstract : T cell suppression prevents acute cellular rejection but causes life‐threatening infections and malignancies. Previously, liver transplant (LTx) rejection in children was associated with the single‐nucleotide polymorphism (SNP) rs9296068 upstream of the HLA‐DOA gene. HLA‐DOA inhibits B cell presentation of antigen, a potentially novel antirejection drug target. Using archived samples from 122 white pediatric LTx patients (including 77 described previously), we confirmed the association between rs9296068 and LTx rejection (p = 0.001, odds ratio [OR] 2.55). Next‐generation sequencing revealed that the putative transcription factor (CCCTC binding factor [ CTCF ]) binding SNP locus rs2395304, in linkage disequilibrium with rs9296068 (D′ 0.578, r 2 = 0.4), is also associated with LTx rejection (p = 0.008, OR 2.34). Furthermore, LTx rejection is associated with enhanced B cell presentation of donor antigen relative to HLA‐nonidentical antigen in a novel cell‐based assay and with a downregulated HLA‐DOA gene in a subset of these children. In lymphoblastoid B (Raji) cells, rs2395304 coimmunoprecipitates with CTCF, and CTCF knockdown with morpholino antisense oligonucleotides enhances alloantigen presentation and downregulates the HLA‐DOA gene, reproducing observations made with HLA‐DOA knockdown and clinical rejection. Alloantigen presentation is suppressed by inhibitors of methylation and histone deacetylation, reproducing observations made during resolution of rejection. Enhanced donor antigen presentation by B cells and its epigenetic dysregulation via the HLA‐DOA gene represent novel opportunities for surveillance and treatment of transplant rejection.